Pemberdayaan Masyarakat Desa Dolat Rayat Melalui Program Sabun Cuci Tangan untuk Meningkatkan Kesehatan dan Ekonomi - Syabilla Putri Affani; Intan Vilja Aura Fazia; Nicholas Faisal Simanjuntak; Aryadino Anggara; Yahfizham Yahfizham (SEWAGATI: Jurnal Pengabdian Masyarakat Indonesia, 2025)
The Real Work Lecture (KKN) program is carried out with the aim of empowering the people of Dolat Rayat Village through hand soap production activities as an effort to improve health while providing sustainable economic added value. The main problem faced by the community is the low awareness of the importance of clean living behaviors and the limited alternative sources of income available in the surrounding environment. This activity includes health counseling on hand hygiene, training on making simple hand soap, packaging assistance, and creative and innovative product marketing strategies. KKN students also provide education about the importance of cleanliness to prevent infectious diseases in the household and school environment. The results of the activity show that the community not only understands the urgency of maintaining hand hygiene, but is also able to develop soap production skills as a sustainable household business opportunity. This program makes a dual contribution, namely increasing awareness of healthy living while opening up opportunities for local economic growth. Thus, this activity proves that the integration of health and the creative economy can be implemented effectively through community empowerment.